PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT PANEN WANGI ABADI - Siti Nur Mala; Usran Masahere (CV Edujavare Publishing, 2024)
PT Panen Wangi Abadi, or Sephora, is a French retail company. The research aims to assess the impact of leadership style and work motivation on employee performance using statistical quantitative methods. The research involved 40 respondents using a saturated sampling technique. The results show that leadership style has a positive and significant effect on employee performance. These results were obtained from the calculated t result of 3.563, which is greater than the t table of 2.026, so this result shows that leadership style has an influence on employee performance and the results of the hypothesis analysis show that leadership style has a positive and significant effect on employee performance. This means that the better the leadership style, the higher the employee performance. These results were obtained from the calculated t of 2.964 which is greater than the t table of 2.026, so these results indicate that leadership style has an influence on employee performance. Leadership Style and Work Motivation together (simultaneously) have a significant effect on the employee performance variable at PT Panen Wangi Abadi.